2015
DOI: 10.1021/acs.jpcc.5b00138
|View full text |Cite
|
Sign up to set email alerts
|

Pt—Si Bifunctional Surfaces for CO and Methanol Electro-Oxidation

Abstract: The bimetallic surfaces offer activity benefits derived from synergistic effects among active sites with uniquely different functions, which is particularly important for the development of highly effective heterogeneous catalysts for specific technological applications, such as energy conversion and storage. Here we report on Pt-Si bulk samples prepared by arc-melting, for the first time, with high activities towards the electro-oxidation of CO and methanol. Increasing the Si concentration on the surface was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…In the previous section on MOR/EOR (section 3.4), one important factor that affects Pt performance is poisoning from the CO intermediate, which strongly deactivates the Pt surface, resulting in higher overpotential and decreased activity [245] . It is therefore important to develop catalysts with high tolerance for CO for DAFCs.…”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous section on MOR/EOR (section 3.4), one important factor that affects Pt performance is poisoning from the CO intermediate, which strongly deactivates the Pt surface, resulting in higher overpotential and decreased activity [245] . It is therefore important to develop catalysts with high tolerance for CO for DAFCs.…”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
“…This could be due to the presence of more Au (110) facets on the 40 nm Au NW, since it was previously demonstrated that when using Au for CO oxidation the reactivity followed the trend Au (110)>Au (100)≫Au (111). In addition, 40 nm diameter Au NWs had a specific activity comparable to a (110) single‐crystal Au surface, making it a good candidate for alloying Pt so that Pt adsorbs alcohol molecules and Au efficiently oxidizes CO to final products [245] …”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
“…Although the overall particle size increased with annealing, the crystallite size of the Pt 3 Sn phase (36 % of the Pt polycrystalline material) was close to 3.4 nm, and that of the PtSn phase was 8.2 nm (64 %, as shown above). [37] Briefly, the preadsorbed À CO ad was oxidized by sweeping the potential at the scan rate of 10 mV s À 1 , starting from the adsorption potential 0.10 V up to 1.20 V where it is fully oxidized. DME adsorption competes with H UPD for platinum sites; hence, in the presence of DME the observed hydrogen adsorption-desorption region is significantly suppressed (3 0 %).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…[3,6,9,10] The measurements were carried out following the procedure described elsewhere. [37] Briefly, the preadsorbed À CO ad was oxidized by sweeping the potential at the scan rate of 10 mV s À 1 , starting from the adsorption potential 0.10 V up to 1.20 V where it is fully oxidized. The oxidation behaviors of Pt/SnO 2 /C (400°C) and Pt/SnO 2 /C (100°C) were compared with a commercial Pt/C (20 wt.% Pt on carbon black) catalyst ( Figure 3c).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…[11][12][13] However, such approach also present difficulties related to the determination of the charge involved in the electrooxidation. For instance, depending on the metal nature, CO can adsorb on different ways onto a surface, 14,15 which can embed errors in estimating the surface area if pure metals are compared with multi-metallic catalysts. Another regular method is normalizing the current by the mass of the main metal (normally Pt) in multi-metallic catalysts.…”
Section: Introductionmentioning
confidence: 99%